Ways To Increase The Efficiency Of Teaching History In Higher Education - Abduvakhidov Dilshod Narbotirovich (Open Academia, 2026)
In the context of modern globalization, one of the main tasks facing the higher education system is to train independent and critically thinking specialists who can ensure the socio-political, cultural and intellectual development of society. The role of history in this process is of particular importance. History appears in higher education not only as an educational subject, but also as an important tool for forming historical thinking, social consciousness, civic position and national identity in students [1, 22]. Today, the process of teaching history in higher education institutions is undergoing a transition from a traditional approach focused on providing knowledge to a competency-based, person-oriented and resultoriented educational model. This creates the need to reconsider the effectiveness of teaching history, adapt its content, methods and technologies to modern educational requirements [2, 45]. In particular, the issue of interpreting historical events not as a set of facts, but based on their causal relationships, social context, and inextricable connection with modernity is becoming increasingly important.
Keywords: civic position; education system; modern globalization